Revisiting intertemporal elasticity of substitution in a sticky price model - Juha Kilponen; Jouko Vilmunen; Oskari Vähämaa (Bank of Finland, 2021)
Macroeconomic models typically assume additively separable preferences where consumption enters the utility function in a logarithmic form. This restriction implies that consumption growth is highly sensitive to movements in real interest rates, which in turn implies an unrealistically steep demand curve and intertemporal trade-off. We re-estimate the stylized New Keynesian Model with US data using King-Plosser-Rebelo (1988) preferences with and without habits and show that the equilibrium real interest rate elasticity of output is in the range of 0.05 - 0.20 in the US. Such low real interest rate elasticity is better in line with the empirical consumption Euler equation literature and implies relatively weak transmission of monetary policy to output and inflation.
URN:NBN:fi:bof-202106091290
Keywords: E32; E52; E21; 330; Monetary policy; Bayesian estimation; Non-separable utility